2013
DOI: 10.1053/j.ajkd.2013.04.010
|View full text |Cite
|
Sign up to set email alerts
|

CKD and Cardiovascular Disease in the Atherosclerosis Risk in Communities (ARIC) Study: Interactions With Age, Sex, and Race

Abstract: Background Estimated glomerular filtration rate (eGFR) and albuminuria are central for diagnosis, staging, and risk evaluation in chronic kidney disease (CKD). Universal thresholds regardless of age, sex, and race are recommended, but relatively little is known about how these demographic factors alter the relationship of eGFR and albuminuria to cardiovascular outcomes. Study Design Observational cohort study. Setting & Participants 11,060 whites and blacks aged 52–75 years in the Atherosclerosis Risk in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
52
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 44 publications
4
52
0
4
Order By: Relevance
“…In a large meta-analysis, Nitsch et al [16] found that the slope of the CV mortality risk relationship was steeper in women, indicating that they were at least as influenced by moderately and severely increased albuminuria as men. Likewise, Hui et al [17] similarly observed stronger associations of ACR with CV morbidity risk in women in a US cohort study (1.3-1.8 fold higher HRs). Our results also indicated higher HRs in women but were not statistically different from men.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In a large meta-analysis, Nitsch et al [16] found that the slope of the CV mortality risk relationship was steeper in women, indicating that they were at least as influenced by moderately and severely increased albuminuria as men. Likewise, Hui et al [17] similarly observed stronger associations of ACR with CV morbidity risk in women in a US cohort study (1.3-1.8 fold higher HRs). Our results also indicated higher HRs in women but were not statistically different from men.…”
Section: Discussionmentioning
confidence: 88%
“…Nitsch et al [16] demonstrated in the 2.1 million CKD-Prognosis Consortium cohort that women have a steeper increase in all-cause and CV mortality risk at ACR levels >2.5 mg/mmol. Hui et al [17] tested possible interactions with age, gender and race in the ARIC cohort with incident CVD as outcome. They found that albuminuria was associated with a higher risk in women.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Tonelli et al 14 reported that, among individuals without a history of previous † Or non-HDL-C=100-219 mg/dl. 10 On the basis of these results, the KDIGO Lipid Work Group concluded that all individuals with CKD $50 years of age should be considered in the highest risk group for future coronary events and treated with statins.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Data from randomized trials have shown that statins reduce the risk for ASCVD events and cardiovascular mortality among individuals with CKD not on dialysis. [6][7][8][9] On the basis of the high absolute risk for ASCVD among individuals with CKD in conjunction with results from clinical trials, the 2013 Kidney Disease Improving Global Outcomes (KDIGO) Foundation Clinical Practice Guideline for Lipid Management in CKD recommended that all adults 50 years of age or older with CKD not on dialysis should be taking a statin.…”
mentioning
confidence: 99%
“…For universal thresholds, the use of this standard is recommended regardless of age, gender, and ethnic group. However, the relation between demographic factors and the impacts of eGFR and albuminuria on CVD is understudied [15].…”
Section: Introductionmentioning
confidence: 99%